2019
DOI: 10.1155/2019/9585964
|View full text |Cite
|
Sign up to set email alerts
|

IL18 Polymorphism and Periodontitis Susceptibility, Regardless of IL12B, MMP9, and Smoking Habits

Abstract: Genetic variations contribute to the susceptibility in the development of periodontitis. The aim of this study was to investigate the influence of IL18, IL12, and MMP9 polymorphisms in the chronic periodontitis. This case-control study involved 381 individuals matched by gender and age. Genotyping of IL18 (rs187238 and rs1946518) and IL12B (rs3212227) was performed by PCR-SSP and PCR-RFLP was used for MMP9 (rs3918242). IL-18 and MMP-9 were quantified in the serum by ELISA. SNPStats and OpenEpi software were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
1
6
0
1
Order By: Relevance
“…After multivariate analysis we observed a tendency (limited by the low statistical power) of men to be predisposed to the disease when in the presence of some polymorphisms in the inflammasome, cytokine and cytokine receptor genes, regardless of cigarette use. Previous studies had found a correlation between immune gene polymorphisms and men's susceptibility to PD [77,78], including Southern Brazilians patients [13,79]. Thus, our data corroborates in emphasizing the importance of genetic factors in men's susceptibility to developing PD.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…After multivariate analysis we observed a tendency (limited by the low statistical power) of men to be predisposed to the disease when in the presence of some polymorphisms in the inflammasome, cytokine and cytokine receptor genes, regardless of cigarette use. Previous studies had found a correlation between immune gene polymorphisms and men's susceptibility to PD [77,78], including Southern Brazilians patients [13,79]. Thus, our data corroborates in emphasizing the importance of genetic factors in men's susceptibility to developing PD.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, genetic and epigenetic factors contribute to the development of PD such as individual differences in the host immune response, smoking habits, gender, poor oral-hygiene, and systemic diseases as diabetes mellitus and rheumatic diseases [1]. Genetic variants that influence the susceptibility and the severity of periodontitis arise from changes that occur in the genes and in the biological molecules that they encode [6,7] including cytokines [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…IL16 polymorphisms were previously studied in PD [23,24]. Other SNPs in cytokine genes such as IL-1β, IL-2, IL-17 and IL-18 were associated with PD in our population from southern Brazil [25][26][27].…”
Section: Introductionmentioning
confidence: 85%
“…Zhan et al., (2014) 7 identified TLR9 ( Toll Like Receptor 9) and IL18 ( Interleukin 18 ) as promising host genes involved in the pathogenesis of periodontitis. IL18 plays an important role in regulating the immunoinflammatory response, modulating macrophage, and neutrophil activity 21 . The Toll‐like receptor (TLR) member 9 ( TLR9 ) belongs to a family of recognition receptors of innate immunity and recognized as one of the most upregulated pattern recognition receptors in chronic periodontitis 22 .…”
Section: Methodsmentioning
confidence: 99%
“…IL18 plays an important role in regulating the immunoinflammatory response, modulating macrophage, and neutrophil activity. 21 The Toll-like receptor (TLR) member 9 (TLR9) belongs to a family of recognition receptors of innate immunity and recognized as one of the most upregulated pattern recognition receptors in chronic periodontitis. 22 From the GWA studies the following genes were found potentially relevant to or significantly associated with periodontal diseases: NPY (Neuropeptide Y), 11…”
Section: Snps Selectionmentioning
confidence: 99%